Organizational Agility Conceptual Model - Rima Zitkiene; Mindaugas Deksnys (Montenegrin Journal of Economics, 2018)
Organizational agility is a complex and multidimensional concept. One of the challenges in researching organizational agility is its unified definition and concept. Literature analysis reveals various dimensions and frameworks are used to analyze organization agility. Many of them focus on narrow industry or only approach the organizational agility concept from limited perspective. This article attempts to combine different approaches and angles to organizational agility to a more cohesive and encompassing conceptual model that is applicable to variety industries and organizations. The variety and combination of attributes, characteristics, capabilities, and practices make the measurement of organizational agility are analyzed. Building on research main frameworks for analyzing organizational agility concept are identified. Conceptual organizational agility model based on organizational agility attributes, capabilities and practices framework is presented. This article contributes to research by providing more unified concept, which can be adapted in studying organizational agility in a wide and global range of organizations, regardless of the industry they operate in.